The Effect of A Learning Organization On Enhancing Digital-Based Human Resource Competencies At The Center For Textiles In Bandung City - Reza Dwiandika; Widwi Handari Adji (Greenation Publisher, 2026)
Digital transformation demands organizations to enhance digital-based human resource competencies by strengthening a Learning Organization culture. This study aims to analyze the effect of a Learning Organization on the enhancement of digital-based human resource competencies at the Center for Textile (Balai Besar Tekstil) in Bandung City. A descriptive quantitative method with a verificative approach was employed. The sample comprised 58 employees out of a total population of 138 employees at the Center for Textile, selected using a simple random sampling technique based on the Slovin formula. Data were collected via questionnaires and analyzed using simple linear regression aided by SPSS 27. The results of the study indicate that the Learning Organization has a positive and significant effect on enhancing digital-based human resource competencies (β = 0.455; p < 0.05), with a coefficient of determination (R2) of 0.314, a t-value of 5.069, and an F-value of 25.690 with a significance value of 0.000. These findings prove that the implementation of a Learning Organization is capable of enhancing human resource competencies through a continuos learning culture; thus, continuously strengthening an organizational learning culture is proven effective in bridging employees’ digital competency gaps.